The Continent Without a Cryohistory? Deep Time and Water Scarcity in Arid Settler Australia - Morgan, Ruth A. (Journal of Northern Studies, 2020)
Australia is a continent seemingly without a cryohistory. But take a closer look. Its cryohistory differs dramatically from that of the northern hemisphere—a contrast that long baffled Victorian geologists seeking evidence of glaciation in the Great South Land. Just as historians have sought to redress the image of a static Arctic through a new attention to its cryohistory, so too historians of Australia have sought to recover a continent that is anything but a “timeless land.” Its long geological history—its cryohistory—framed Aboriginal lifeways across the continent, which in turn, shaped colonial encounters in the aftermath of British invasion in 1788. Guiding this historical project have been the moral challenges of the settler nation’s legacy of Indigenous dispossession and displacement, and the unfolding planetary crisis of the Anthropocene and its implications for critically understanding deep time. This article examines the colonial hydrology of water scarcity in the goldfields of arid Western Australia in the late nineteenth century. It shows how access to freshwater became a flashpoint for relations between Indigenous and non-Indigenous peoples on an extractive frontier. At the turn of the twentieth century, water was the means by which to improve health, hygiene and cleanliness, without which the privileges of white civilisation could not be afforded. Although such conditions also developed elsewhere in settler Australia, the limited water availability on the eastern goldfields made the circumstances that emerged there especially dire. Accordingly, the material conditions of the arid inland—the product of Australia’s Pleistocene—came to bear on the nature of the encounters between Indigenous and non-Indigenous peoples from the mid-nineteenth century. The very absence of ice in Australia’s cryohistory left its mark on the peoples of the eastern goldfields.